Study of The Acid-Base Effect on Zeolite Activation and Its Characterization as Adsorbent of Methylene Blue Dye - Yulius Dala Ngapa (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
Activation is one of the processes by which are mostly done to improve the quality of natural zeolite. Activation process by zeolite will change the ratio of the Si/Al and can increase the formation of empty cavities so that the capability of zeolite as an adsorbent be optimal. In this research, natural zeolite from the district of Ende, Nusa Tenggara Timur. Activation Ende natural zeolite done chemically using HCl and NaOH solution, with variations concentrate 0,5 M; 1,5 M; and 3,0 M. Next, zeolite which has activated used to adsorb dye methylene blue. Based on the research results, chemically of activation from natural zeolite can increase the adsorption capacity to substance methylene blue. The adsorption capacity in the Ende natural and after activation is 17,289 mg/g and 19,98 mg/g respectively. The Langmuir model most closely matched the isothermal adsorption of equilibrium process.